Evidence for public health policy on inequalities: 1: The reality according to policymakers. Issue 10 (13th September 2004) - Petticrew, Mark; Whitehead, Margaret; Macintyre, Sally J; Graham, Hilary; Egan, Matt
Abstract : Objective: To explore with UK and international policy advisors how research evidence influences public health policy making, and how its relevance and utility could be improved, with specific reference to the evidence on the production and reduction of health inequalities. Design, setting, and participants: Qualitative residential workshop involving senior policy advisors with a substantive role in policy development across a range of sectors (mainly public health, but also including education, social welfare, and health services). In four in depth sessions, facilitated by the authors, focused questions were presented to participants. Their responses were then analysed thematically to identify key themes, relating to the availability and utility of existing evidence on health inequalities. Main results: The lack of an equity dimension in much aetiological and evaluative research was highlighted by participants. Much public health research was also felt to have weak underlying theoretical underpinnings. As well as evaluations of the effectiveness and cost-effectiveness of policy and other interventions, they identified a need for predictive research, and for methodological research to further develop methods for assessing the impact on health of clusters of interventions. Conclusions: This study reinforces the view that there is a lack of information on the effectiveness and cost-effectiveness of policies, and it uncovered additional gaps in the health inequalities evidence base. A companion paper discusses researchers' views of how the production of more relevant public health evidence can be stimulated.